NILAI TAMBAH USAHA PENGOLAHAN IKAN ASAR DI PANTAI TANJUNG MARTHAFONS DESA POKA - Eygner Gerald Talakua; Yofita Anaktototy; Bryan Ohello (Universitas Pattimura, 2022)
In early 2019, an asar fish processing business appeared on Tanjung Marthafons Beach, Poka Village. The advantage of this business is that it utilizes fresh cultivated fish, fish at the bottom and directly served for consumption. This business requires basic data for business development and sustainability. This study aims to analyze the added value of asar fish processing business on the Coast of Marthafons Cape in Poka Village. The survey was conducted in four business units, with the key respondents being business owners. The data obtained through observation and interviews were then analyzed using the value-added method of processing business. The results showed that the smoked fish processing business on the Coast of Marthafons Cape in Poka Village which consisted of the Marthafons, G & J Café, Lolias, and Mega Fish business units had an added value of Rp 27,620 to Rp 45,864 per kg. The value-added ratio shows that the G & J Café and Lalosi business units have low value-added, while the Marthafons and Mega Fish business units have moderate value-added. This value-added provides business certainty due to the high profit ratio of 78.52% to 96.90% per production period.